The Determinants of Income Inequality in Malaysia - Regina Lee, Junup (Universiti Malaysia Sarawak (UNIMAS), 2022)
The goal of this study is to look at the determinants that conritbute to income inequality in Malaysia. The time series spans the years 1990, with 30 observations. The data was analyzed using E-views software which consists of several methods used in this study. The tests that have been employed in this study include unit root tests, namely the Augmented Dickey-Fuller (ADF) test and Phillips-Perron (PP) test; cointegration test of Johansen and Juselius; Granger causality test based on Vector Error Correction Model (VECM) to investigate the long run and short run relationship and also diagnostic tests to check the stability of the variables in the model. The result reveals that economic growth, education level, and inflation rate have long-run and short-run relationships with income inequality in Malaysia. Hence, the economic growth and inflation rate have a significant relationship towards income inequality in Malaysia while education level has an insignificant relationship toward income inequality in Malaysia. Thus, the government needs to implement and introduce new ways and solutions in increasing and enhancing the quality of the education system that could aid in reducing the country’s income inequality.